Deskripsi Kesalahan Siswa Dalam Menyelesaikan Soal Matematika Materi Bangun Ruang di Kelas V SDN 16 Sungai Pinyuh - Maisaroh, Maisaroh (PT. ALHAFI BERKAH INDONESIA, 2024)
This research identified five types of errors made by students in solving mathematical problems about spatial figures, namely errors in reading the problem, errors in understanding the problem, errors in problem transformation, process skills errors, and errors in writing the final answer. The aim of this research is to describe the types of errors and the number of students who make each type of error. This research uses a descriptive qualitative approach with test question sheet instruments and collects data through documentation. The main data source is 21 fifth grade students and their answers from the 2023 school year. The research results show that 14.2% of students made mistakes in reading the questions, 19.0% of students made mistakes in understanding the problems, 15.4% of students made mistakes in problem transformation, 46.4% of students made process skills errors, and 57.1% of students made errors in writing the final answer. These types of errors reflect the various problems students face in solving mathematical problems on geometric material.